STUDI KASUS PROSEDUR PEMERIKSAAN HYSTEROSALPINGOGRAPHY DENGAN KLINIS INFERTILITAS PRIMER DI INSTALASI RADIOLOGI RSUD TIDAR KOTA MAGELANG - Fifi Fitriana Bahi; Fisnandya Meita Astari; Retno Wati (Journal of Innovation Research and Knowledge, 2025)
Background: Hysterosalpingography is an important examination in diagnosing infertility, aimed at assessing the patency of the fallopian tubes and identifying causes of obstruction or abnormalities in the uterine cavity. The hysterosalpingography examination for primary infertility at the Radiology Installation of RSUD (Regional General Hspital) Tidar, Magelang City, utilizes plain AP pelvis projection, AP, and RPO post-contrast projections with a two-stage contrast media introduction. However, there are differences in projections and contrast media introduction compared to previous studies. This research aims to understand the procedure and the reasons for using AP and RPO projections without LPO, as well as the rationale for introducing 15 ml of contrast media in two stages: 10 ml for AP and 5 ml for RPO. Methods: This study employed a qualitative case study approach. The research was conducted at the Radiology Installation of RSUD Tidar, Magelang City, from August 2024 to January 2025. The subjects of the study included three radiographers and one radiology specialist. The object of the research was the hysterosalpingography examination. Data were collected through observations, interviews, literature studies, and documentation. Data analysis involved data reduction, data presentation, discussion, and conclusion drawing. Results: The hysterosalpingography examination procedure for primary infertility at the Radiology Installation of RSUD Tidar, Magelang City, included patient preparation, equipment and material preparation, contrast media introduction, and examination techniques. The reason for including only the RPO projection without LPO was that the right fallopian tube spill was not yet visible, while the left fallopian tube spill was already visible in the AP projection. The first stage of contrast media introduction involved 10 ml for the AP projection to visualize the uterine cavity and fallopian tubes, while the second stage involved 5 ml for the RPO projection to visualize the right fallopian tube and spill into the peritoneal cavity that was not yet visible in the first stage. Conclusions: The hysterosalpingography examination for primary infertility at the Radiology Installation of RSUD Tidar, Magelang City, was performed using AP and RPO post-contrast projections without LPO, as the left fallopian tube spill was already visible in the AP projection. The rationale for the two-stage contrast media introduction was to optimize the visualization of anatomy and the spill from the fallopian tubes into the peritoneal cavity